Razrabotka osnov nauchnogo kommunizma. Bor'ba za sozdaniye proletarskoy partii. 1844-1848 gg.
Black and white scans of manuscripts, paintings, and maps depicting Marx and Engels' role in the events of 1848 Original title: Разработка основ научного коммунизма. Борьба за создание пролетарской партии. 1844-1848 гг. PO-0606